FORM AND COMPOSITION OF LOCAL GOVERNMENT: MIXED REVIEW REGIONAL GOVERNMENT YOGYAKARTA - Triwahyuningsih Triwahyuningsih (Surakarta Law and Society Journal, 2019)
This study aims to analyze and explain shape and composition of government Special Region of Yogyakarta that is privileged, reviews mixed government. This study is a normative legal research. The results of the study that Yogyakarta Special region has a shape and structure of government is unique in nature. DIY Local Government consists of Local Government and DPRD DIY DIY. DIY Local Government headed by the Governor who once was a king who reigns as the lane, who held the position for five (5) years and are not bound to the provisions of 2 (two) times periodization tenure as stipulated in the law on local government. DIY DPRD have the status, composition, duties and authority as provided for in the legislation Regional Government, as applicable also to Parliament in another province. However, in addition to duty and authority as specified Local Government Act, DIY Parliament is authorized to determine governor and vice governor and shaping legislation and Perdais with the Governor. The combination of the Governor of Yogyakarta as the king who reigns in the Sultanate along with a DIY parliament democratically elected government raises mixture (mixed government) in the form of democratic monarchy.